التعادل الوظيفي في الإثبات بين المحرر التقليدي والإلكتروني في التشريع الجزائري - حويذق, عثمان; ذهب, خليفة (University of Eloued جامعة الوادي, 2021)
In light of the amazing electronic development that the world is witnessing and the changes taking place in the field of technology, a new style of writing and signature has emerged, since the traditional means used in proof may not be compatible with the secretions of modern development. Thus, the transition was made from the tangible realistic form to the digital virtual form, which led to the recognition of the electronic evidence in terms of strength and authenticity until it became a complete Guide of proof.
مداخلة. الملتقى الدولي السادس عشر حول الإثبات الالكتروني في المواد المدنية والجزائية بين الاطلاق والتقييد. كلية الحقوق والعلوم السياسية. جامعة الوادي
Keywords: التعادل الوظيفي، الاثبات، المحرر التقليدي، المحرر الإلكتروني، التشريع الجزائري